Peningkatan Hasil Belajar Matematika Tentang Pecahan Melalui Model Interaktif pada Siswa SD - Rokhaniyah Rokhaniyah (Fakultas Keguruan dan Ilmu Pendidikan, 2018)
This study aims to determine the problems that occur in learning mathematics about fractions and find ways to solve these problems. The focus of the problem under study is